2020
DOI: 10.1111/nph.16860
|View full text |Cite
|
Sign up to set email alerts
|

Two metallothionein genes highly expressed in rice nodes are involved in distribution of Zn to the grain

Abstract: A rice node is a hub for distribution of mineral elements; however, most genes highly expressed in the node have not been functionally characterized. Transcriptomic analysis of a rice node revealed that two metallothionein genes, OsMT2b and OsMT2c, were highly expressed in the node I. We functionally characterized these genes in terms of gene expression pattern, cellular and subcellular localization, phenotypic analysis of the single and double knockout mutants and metal-binding ability. Both OsMT2b and OsMT2c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 54 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Little is known how Cd and metals are transported from the nodes into the phloem. For Zn, rice mutants with knocked out genes that encode metallothionein in node I decreased the Zn transport from the node to the grain ( Lei et al, 2020 ). These proteins with S donor ligands seem to bind Zn also in the companion cells that are directly connected to the phloem without a membrane that separates these cells from the phloem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known how Cd and metals are transported from the nodes into the phloem. For Zn, rice mutants with knocked out genes that encode metallothionein in node I decreased the Zn transport from the node to the grain ( Lei et al, 2020 ). These proteins with S donor ligands seem to bind Zn also in the companion cells that are directly connected to the phloem without a membrane that separates these cells from the phloem.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Cd to organic ligands may impact the transfer of metals through membranes ( Zhao et al, 2016 ). In a next step, Cd storage forms could be coupled with membrane transporters by comparing wild-type and mutant plants that lack or overexpress specific membrane transporters ( Cadiou et al, 2017 ; Pokharel et al, 2018 ; Lei et al, 2020 ; Moore et al, 2020 ; Wiggenhauser et al, 2021 ; Zhang et al, 2021 ).…”
Section: Implications and Outlookmentioning
confidence: 99%
“…OsVIT1 and OsVIT2 are expressed primarily in flag leaves and, as such, loss-of-function osvit1 and osvit2 mutants show increased Fe and Zn concentrations in seeds, and reduced accumulation in source flag leaves due to impaired vacuolar storage in the leaf blade (Zhang et al, 2012). In rice, MTs OsMT2b and OsMT2c are expressed in the phloem of enlarged vascular bundles of nodes, and play an important role in Zn distribution to grains through Zn chelation and transport in the phloem (Lei et al, 2021). osmt2b and osmt2c knockout mutants show increased accumulation of Zn in nodes and reduced Zn in the panicle, and subsequently impacted grain yield (Lei et al, 2021).…”
Section: Zn Accumulation In Seeds and Grainsmentioning
confidence: 99%
“…In rice, MTs OsMT2b and OsMT2c are expressed in the phloem of enlarged vascular bundles of nodes, and play an important role in Zn distribution to grains through Zn chelation and transport in the phloem (Lei et al, 2021). osmt2b and osmt2c knockout mutants show increased accumulation of Zn in nodes and reduced Zn in the panicle, and subsequently impacted grain yield (Lei et al, 2021). More detailed information on the transport of Zn within seeds can be found in Olsen and Palmgren (2014).…”
Section: Zn Accumulation In Seeds and Grainsmentioning
confidence: 99%
“…In a recent study, OsZIP4 was found to transport Zn to the phloem of diffuse vascular bundles in the node, leading to the efficient distribution of Zn to tiller buds and other developing tissues (Mu et al 2020 ). Additionally, two metallothionein genes, OsMT2b and OsMT2c , which are highly expressed in node I in rice, were demonstrated to distribute Zn to grains through chelation (Lei et al 2021 ). These molecular studies uncovered the mechanism of Zn distribution in rice and will enable the fine tuning of the efficient distribution of Zn in the edible parts of many crops.…”
Section: Introductionmentioning
confidence: 99%